P222 Pleural TB: a common cause of pleural effusion in South London. (14th November 2013) - Pickering, O; Sarefuji, R; Ahmed, L; Breen, R; Milburn, H
Abstract : Background: Pleural tuberculosis (TB) is one of the most common forms of extrapulmonary TB, reported to account for up to 25% of TB infected adults, and 30% of exudative pleural effusions in developing countries. Despite this, little information has been reported on its incidence within London. Aims and methods: A retrospective observational study was performed at a London tertiary referral centre. The aim was to identify the contribution of pleural TB to the overall burden of both pleural and TB disease, and assess diagnostic yields of investigation techniques and outcomes of treatment. Results: 28 patients were diagnosed with pleural TB between Jan 1 st 2010- 31 st Dec 2012. This represented 6.2% of the total number of TB cases, and 4% of the total number of investigated pleural disease cases. The mean age of the patients was 33 ± 10 (range 17–62); 79% were male; 46% were Black African, 29% Asian, 21% Caucasian and 4% Black Caribbean. There was a range of symptoms at presentation, with 96% of patients complaining of at least one symptom (Figure 1 ). Diagnostic yields were as follows; sputum smear 3% and culture 18%; pleural fluid smear 0 and culture 36%; pleural biopsy smear 11% and culture 54%; pleural biopsy histology 93%. Culture yield for pleural fluid and biopsy was 61%, and overall culture yield for sputum, pleural fluid and biopsy was 68%. All patients' received quadruple TB therapy, with 82% of patients being given the standard six-month therapy. 92% showed an excellent radiological response, with the x-ray being normal, or with only minor residual abnormalities. To the present date, there has been no diagnosed recurrence of TB. Conclusions: Pleural TB contributes significantly to the overall burden of pleural disease in this London hospital. TB should be considered in patients presenting with pleural disease, especially young patients from ethnic minority backgrounds. To improve the diagnosis and treatment of pleural TB, culture yields need improvement.